2008
DOI: 10.1007/s00253-007-1276-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production of ellagic acid and biodegradation of ellagitannins

Abstract: In the last years, tannin biodegradation has been the subject of a lot of studies due to its commercial importance and scientific relevance. Tannins are molecules of low biodegradation and represent the main chemical group of natural anti-microbials occurring in the plants. Among the different kinds of tannins, ellagitannins represent the group less studied manly due to their diversity and chemical complexity. The general outline of this work includes information on tannins, their classification and properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 83 publications
1
59
0
2
Order By: Relevance
“…Condensed tannins are oligomeric and polymeric proanthocyanidins containing flavan-3-ol (catechin) or flavan-3,4-diol linked by C-Cbonds. The basic structure of complex tannins consists of a gallotannin or ellagitannin unit and one of catechin (Belmares et al 2004;Aguilera-Carbó et al 2008).…”
Section: Tanninsmentioning
confidence: 99%
“…Condensed tannins are oligomeric and polymeric proanthocyanidins containing flavan-3-ol (catechin) or flavan-3,4-diol linked by C-Cbonds. The basic structure of complex tannins consists of a gallotannin or ellagitannin unit and one of catechin (Belmares et al 2004;Aguilera-Carbó et al 2008).…”
Section: Tanninsmentioning
confidence: 99%
“…Several medicinal and industrial applications have been found for this acid such as, antitumoral, antioxidant, antimicrobial, antiviral, antiflamatory activities; in addition reduce the heart diseases (Aguilera-Carbó et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Based on sugar content and degrees of polymerization and esterification, tannins are classified into condensed, hydrolysable and complex classes (Khanbabaee and van Ree, 2001;Aguilera-Carbo et al, 2008). Owing to their astringency and the ability to form complexes with proteins and polysaccharides, tannins serve to protect plants against attack by parasites and herbivores.…”
Section: Introductionmentioning
confidence: 99%